1998
DOI: 10.1136/jmg.35.8.617
|View full text |Cite
|
Sign up to set email alerts
|

Hirschsprung disease, microcephaly, mental retardation, and characteristic facial features: delineation of a new syndrome and identification of a locus at chromosome 2q22-q23.

Abstract: We have identified six children with a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
232
1
6

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(254 citation statements)
references
References 19 publications
(3 reference statements)
12
232
1
6
Order By: Relevance
“…MWS was first delineated by Mowat et al 1 as a syndromic condition characterized by distinctive facial phenotype, ID, and Hirschsprung disease in four of six reported individuals. The causative genetic defect was mapped to chromosome 2q21-q23 based on cytogenetic deletions in two patients, 1,2 and narrowed to heterozygous mutations of the ZEB2 gene by subsequent reports.…”
Section: Mowat-wilson Syndrome (Mws) (Omim # 235730) Ismentioning
confidence: 99%
“…MWS was first delineated by Mowat et al 1 as a syndromic condition characterized by distinctive facial phenotype, ID, and Hirschsprung disease in four of six reported individuals. The causative genetic defect was mapped to chromosome 2q21-q23 based on cytogenetic deletions in two patients, 1,2 and narrowed to heterozygous mutations of the ZEB2 gene by subsequent reports.…”
Section: Mowat-wilson Syndrome (Mws) (Omim # 235730) Ismentioning
confidence: 99%
“…[51][52][53][54][55][56][57][58] Some of the diagnoses which must be excluded in this group are Rett syndrome, 59 60 the α thalassaemiamental retardation syndrome, 61 and the condition described by Mowat et al, which is now known to be the result of large scale deletions or point mutations within the ZFHX1B gene on chromosome 2. 62 63 The diagnosis of AS may also be considered in children with broader symptom complexes, such as cerebral palsy, Lennox-Gastaut syndrome, or mitochondrial disorders. 15 22 64 Williams et al 65 summarised many of the conditions which mimic Angelman syndrome and a comprehensive list is given in table 3.…”
Section: Genetics Of Angelman Syndromementioning
confidence: 99%
“…Because of parental consanguinity [Hurst et al, 1988] and sib recurrence in three families [Goldberg and Shprintzen, 1981;Kumasaka and Clarren, 1988;Yomo et al, 1991] autosomal recessive inheritance has been proposed. In 1998, Mowat et al reported 6 sporadic patients (®ve with HSCR, one with constipation) who shared the same distinctive facial appearance, microcephaly, and mental retardation, different from the original patients described by Goldberg and Shprintzen [Mowat et al, 1998]. They recognized the same facial appearance in three previously published patients [Hurst et al, 1988, case 3;Tanaka et al, 1993;Lurie et al, 1994].…”
Section: Introductionmentioning
confidence: 72%